Pharmacologically-induced mitotic synchrony in airway epithelial cells as a mechanism of action of anti-inflammatory drugs. Issue 1 (December 2015) - Freishtat, R; Nino, G; Tsegaye, Y; Alcala, S; Benton, A; Watson, A; Reeves, E; Haider, S; Damsker, J
Abstract Background Mitotic synchrony is the synchronous progression of a population of cells through the cell cycle and is characteristic of non-diseased airway epithelial cells. However, we previously showed that asthmatic airway epithelial cells are characterized by mitotic asynchrony and are pro-inflammatory as a result. Glucocorticoids can induce mitotic synchrony that in turn suppresses the pro-inflammatory state of diseased cells, suggesting a novel anti-inflammatory mechanism of action. Herein, we benchmarked traditional glucocorticoids against the ability of a new clinical-stage dissociative steroidal drug, VBP15, for mitotic resynchronization and associated anti-inflammatory activity in asthmatic airway epithelial cells. Methods Primary airway epithelial cells differentiated at air-liquid interface were exposed to VBP15, dexamethasone or vehicle following in vitro mechanical injury. Basolateral cytokine secretions (TGF-β1, IL-6, IL-10, IL-13, and IL-1β) were analyzed at different time points using cytometric bead assays and mitosis was examined by flow cytometry. Results VBP15 improved mitotic synchrony of proliferating asthmatic cells in air-liquid interface cultures compared to vehicle-exposed cultures. VBP15 also significantly reduced the basolateral secretion of pro-inflammatory (i.e. IL-1β) and pro-fibrogenic cytokines (i.e. TGF-β1) in air-liquid interface-differentiated asthmatic epithelial cultures following mechanical injury. Conclusion VBP15 improves mitotic asynchrony and injury-induced pro-inflammatory and fibrogenic responses in asthmatic airway epithelial cultures with efficacy comparable to traditional glucocorticoids. As it is predicted to show superior side effect profiles compared to traditional glucocorticoids, VBP15 holds potential for treatment of asthma and other respiratory conditions.